Leukoencephalopathies in Adulthood - Tillema, Jan-Mendelt; Renaud, Deborah L. (Seminars in Neurology, 2012)
The understanding of the genetic basis of late-onset leukoencephalopathies has continued to increase in recent years. The most commonly presenting leukoencephalopathies in adulthood can be late-onset manifestations of metabolic pathways. The understanding of these diagnoses is crucial to the evaluation of adult patients presenting with leukoencephalopathies. The authors provide an overview of the common leukoencephalopathies in adulthood, the current understanding of the pathology, and genetics of these disorders with typical imaging findings. When available, treatment options will be discussed.
Keywords: leukodystrophy; leukoencephalopathy; adult-onset; autosomal dominant